Characteristics Analysis of the Archimedes Screw Turbine Micro-hydro Power Plant with Variation of Turbine Elevation Angle - Muhammad Arief Bustomi; Bachtera Indarto; Afif Mahrus Kurnia Putra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2021)
Electrical energy has become a basic need of modern society, but the supply of electricity has not yet fully met the needs of the community. Many potential energy sources can be converted into electrical energy. One potential of energy sources is water flow which can be used for micro-hydro power plants in remote areas. This study aims to analyze the characteristics of the Archimedes screw turbine of micro-hydro power plant, in particular concerning on variations in the elevation angle of the turbine. Characteristics determination was carried out on a prototype of a micro-hydro power plant using a Brush Less Direct Current (BLDC) generator and two blades of Archimedes screw turbine. The varied turbine elevation-angle was applied, namely 20, 25, 30, 35, and 40o, with a water discharge of 2.64 L/s. The results show that an increase in the turbine elevation angle from 20 to 40o causes an enhancement in mechanical characteristics, i.e. torque and rpm, as well as electrical characteristics, i.e. voltage, current, and electric power. The mechanical and electrical characteristics reach a maximum value at the elevation angle of about 30o, which is 27.87 mW at 1 kΩ load. Furthermore, increasing the elevation angle to become more than 30o causes a decrease in mechanical and electrical characteristics.